2020
DOI: 10.3390/su12187688
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Approach to Trip Generation Modeling for Urban Residents and Non-local Travelers

Abstract: Trip generation modeling is essential in transportation planning activities. Previous modeling methods that depend on traditional data collection methods are inefficient and expensive. This paper proposed a novel data-driven trip generation modeling method for urban residents and non-local travelers utilizing location-based social network (LBSN) data and cellular phone data and conducted a case study in Nanjing, China. First, the point of interest (POI) data of the LBSN were classified into various categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This test is used to determine whether or not the model is stationary. It represents that whether the explanatory components in the model have a consistent correlation with the dependent variable in both geographic and data space (Mitchel and Griffin, 2005;Yang et al, 2020).…”
Section: Model Stationarymentioning
confidence: 99%
“…This test is used to determine whether or not the model is stationary. It represents that whether the explanatory components in the model have a consistent correlation with the dependent variable in both geographic and data space (Mitchel and Griffin, 2005;Yang et al, 2020).…”
Section: Model Stationarymentioning
confidence: 99%
“…Another reason for using Big Data is the enormous increase in the amount of passively collected location data that are available. Research on the use of LBSN data for supply-demand transportation is advancing and ongoing [6], including trip generation and [7] trip distribution modeling [8], as well as trip destination selection [9]. It is clear, though, that research on the use of LBSN data for transportation system modeling is not yet comprehensive and in-depth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The point radius number is expressed in latitude, longitude, and radius and is entered in the data collection program script. Twitter limits the data capture radius to less than 25 miles (40.2 km) [7]. Since there are two techniques for retrieving data, another question arises: whether streaming data or historical data alone are sufficient, or do both methods need to be used to provide enough data for the modeling?…”
Section: Literature Reviewmentioning
confidence: 99%
“…This approach was considered less tedious when compared to the time and effort spent on traffic data collection. Yang et al [36] demonstrated the use of a random forest regression approach to model trip generation for resident and non-resident trip-makers of 36 zones in Nanjing city in China using cell phone signals collected from 76,061 signal towers. The study indicated that the trip-making characteristics of resident and non-resident trip-makers of the city varied significantly and that mixed land use influenced trip generation.…”
Section: Mustafa and Zhongmentioning
confidence: 99%